Mechanical properties of solid and porous stainless steel sheet material at elevated temperatures - Lord, J. B. (College of Aeronautics, 1960)
A series of tensile tests in the temperature range from 20 o C to 1000 o C were carried out on three stainless steel sheet materials, namely D. T.D.166B, D. T. D. 171 and a woven porous material called Rigimesh. Values of Young's modulus, secant modulus, proof stress and ultimate stress were determined over the whole temperature range, and values of Poisson's ratio were determined at temperatures up to 500 o C. Room temperature tests were also carried out on the woven material at various orientations of the weave.